Developing dashboards for SMEs to improve performance of productive equipment and processes - Vilarinho, Sandrina Fátima Soares (2018)
Developing and implementing dashboards is common in large companies. However, these practices should be adapted to small and medium enterprises (SMEs), since they differ in several characteristics, including at information system level. This paper proposes a procedure to develop dashboards for SMEs aimed at improving the performance of productive equipment and processes, at shop floor level. The developed dashboard intends to improve performance by efficiently providing information to the productive areas and turn this information into knowledge, plans, and actions which promote an effective shop floor activity. The main phases of the proposed procedure are defined based on the traditional process of product development. One of the main phases, the development of the dashboard layout, was performed considering visual management and continuous improvement approaches, such as kaizen and Total Productive Maintenance. The development of an adequate data source that feeds the data into the dashboard is also considered in the procedure. In order to achieve an effective dashboard, its development should consider the level of quality maturity of the company, as well as, the maturity of the information and communication system. The proposed procedure assists SMEs in achieving a dashboard to improve the performance of productive areas, improving productive information and communication and promoting a culture of continuous improvement at shop floor level.